The potential impact of NIPT as a second-tier screen on the outcomes of high-risk pregnancies with rare chromosomal abnormalities - Maxwell, S.; Dickinson, J.; Murch, A.; O'Leary, Peter (Blackwell Publishing, 2015)
© 2015 The Royal Australian and New Zealand College of Obstetricians and Gynaecologists. Aim To describe the potential impact of using noninvasive prenatal testing (NIPT) as a second-tier test, on the diagnosis and outcomes of pregnancies identified as high risk through first trimester screening (FTS) in a cohort of real pregnancies. Materials and Methods Western Australian FTS and diagnostic data (2007-2009) were linked to pregnancy outcomes. Karyotype results from invasive prenatal testing in high-risk women were analysed. The outcomes of abnormal results that would not be detected by NIPT, assuming a panel of trisomy 21/18/13 and sex chromosome aneuploidies, and the likelihood of diagnosis in a screening model using NIPT as a second-tier test are described. Results Abnormal karyotype results were reported in 224 of 1488 (15%) women with high-risk pregnancies having invasive diagnostic testing. NIPT potentially would have identified 85%. The 33 abnormalities unidentifiable by NIPT were triploidies (n = 7, 21%), balanced (n = 8, 24%) and unbalanced rearrangements (n = 10, 30%) and level III mosaicisms (n = 8, 24%). For conditions not identifiable by NIPT, fetal sonographic appearance was likely to have led to invasive testing for 10 of 17 (59%) pathogenic abnormalities. If a policy was adopted recommending invasive testing for FTS risk >1:50 and/or ultrasound detected abnormality, the residual risk of an unidentified pathogenic chromosomal abnormality in those without a diagnosis would have been 0.33% (95% CI 0.01-0.65%). Conclusions A screening model with NIPT as a second-tier for high-risk pregnancies would be unlikely to have changed the outcome for the majority of pregnancies. Optimising the diagnosis of rare pathogenic abnormalities requires clear indicators for invasive testing over NIPT.